Pengaruh Motivasi Intrinsik, Motivasi Ekstrinsik, dan Gaya Kepemimpinan Transformasional terhadap Kepuasan Kerja Pegawai Satuan Polisi Pamong Praja Kabupaten Gunungkidul - Alifian Dandy Aswara; Ignatius Soni Kurniawan (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to analyze the effect of intrinsic motivation, extrinsic motivation, and transformational leadership style on job satisfaction in Satuan Polisi Pamong Praja Kabupaten Gunungkidul. Multiple linear regression analysis was used to analyze the effect of the independent variables on the dependent variable. The population in this study were all employees at Satuan Polisi Pamong Praja Kabupaten Gunungkidul and the sample size used was 90 employees. The results showed that intrinsic motivation, extrinsic motivation, and transformational leadership style partially have a positive influence on job satisfaction. Keywords: transformational leadership style; job satisfaction; extrinsic motivation; intrinsic motivation.